PENGARUH PENGGUNAAN EXPANSION VALVE BERBAHAN DASAR MATERIAL KONDUKTIVITAS RENDAH TERHADAP PERFORMA AC MOBIL DINAS TNI-AD JENIS ISUZU PANTHER - Bambang HP; Taufan Tjandra_Kusuma; Suhendro Oktosatrio (JURNAL MEKANIKASISTA, 2022)
Comfort in vehicles is usually by using a conditioning system (Air Conditioning system).AC is a type of engine that works that follows the thermodynamic cycle, namely the vapor compression cycle.A refrigeration machine depends on the ability of the compressor to meet the amount of refrigerant gas that needs to be circulated. Compressor is a tool for pumping refrigerant (refrigerant) to keep circulating in the system. The performance of the car air conditioning compressor is controlled by a thermostat, where this thermostat gives an active or inactive signal adjusted in the car temperature has been reached or not the temperature in the car. This study includes variations in cooling load with a fixed compressor rotation is 759 RPM, each variation of the cooling load is tested with a fixed compressor rotation of 759 RPM by using one refrigerant R-134a to determine the COP, then this study continued by calculating the time of life and death of the compressor to save energy used.The results of the research conducted that the greater the cooling load, the pressure in the compressor and the pressure out of the compressor (3P = P1 – P2 ) the greater.